Self-Esteem and Resilience Differences Among Street Children Compared to Non-street Children in Limpopo Province of South Africa: A Baseline Study - Maepa, Mokoena Patronella (Frontiers in Public Health, 2021)
The phenomenon of street children is a challenging global social problem. Using an independent sample group design, this study explored the differences in self-esteem and resilience among street children and non-street children. A total of 300 (N = 300) street children with ages ranging from 8 to 18 years were selected using a purposive sampling method, while a total of 300 (N = 300) non-street children with ages ranging from 8 to 18 years were selected using a simple random sample to participate in this study. A questionnaire with three sections was used to collect data. Results of an independent sample t-test revealed that street children reported low self-esteem and poor resilience compared to non-street children. The study, therefore, concluded that street children and non-street children differ on self-esteem and resilience. It is recommended that social skills training be provided for the street children population.